PEMBELAJARAN TEKS DRAMA BERDASARKAN KURIKULUM 2013 PADA KELAS XI SMA NEGERI 1 SUNGAI AMBAWANG - Maradika, Puja; Priyadi, Antonius Totok; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by high school drama text learning which is still suspected to have constraint, this is because in general the teacher in delivering the material is not in accordance with the planned implementation of learning that has been designed. Common problems in this study are planning, implementation, and learning outcomes. The general purpose of this research is to describe the learning of drama text based on the curriculum of 2013 on the students of class XI IIS semester 2 SMA Negeri 1 Â Sungai Ambawang. The method used in the research is descriptive method because the research describes the planning, implementation and learning outcomes implemented by teachers. The form of this research is qualitative data in the form of words. Research data is teacher planner made by teacher, implementation of learning in class and result obtained by student. Sources of data in the study were Indonesian students and teachers.it can be concluded that the planning made by the teacher is in accordance with the planning component. Implementation of lessons learned by teachers is less appropriate with planning. The value obtained by students is 71.88 still under KKM.Â Keywords: Learning, Drama Text, Curriculum 2013Â